Perbandingan Sinyal Jual dan Sinyal Beli Pada Saham Perbankan Syariah: Analisis Teknikal Dengan Indikator Moving Averange Convergence Divergence (MACD) dan Relative Strength Index (RSI) Periode 2018 – 2022 - Caristanica, Viona; Wanodya, Rachma Ayu; Wulandari, Catur; Yudiantoro, Deni (FEB Universitas Maritim Semarang, 2024)
The research focuses on identifying sell signals and buy signals in stock buying and selling transactions using technical analysis used by investors to achieve optimal profits. This study compares the influence of MACD and RSI indicators on sell signals and buy signals before and after using Islamic banking stocks listed on IDX. Next, to find out which indicator is more effective in identifying sell and buy signals. The research method used is quantitative with a descriptive research design . The data analyzed is secondary data obtained from data samples from PT. Bank Syariah Indonesia Tbk, PT. Bank BTPN Syariah Tbk, PT. Bank Panin Dubay Syariah Tbk, PT. Bank Aladin Syariah Tbk for the period 2018-2022. The result of the study is that there is no significant difference between sell signals and buy signals before and after the use of the Moving Avergence Convergence Divergence indicator and the Relative Strength Index indicator. Based on the t-test, each indicator states that using the RSI indicator has a positive value.